Pengaruh Lingkungan Kerja, Stres Kerja dan Work Family Conflict Terhadap Kinerja Pegawai (Studi Kasus Pegawai Puskesmas Dinoyo) - Anggun Febi Jayanti; Pardiman Pardiman; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research was conducted on employees of Dinoyo Health Center. This study aims to analyze the influence of the work environment on employee performance, to analyze the effect of work stress on employee performance, to analyze the effect of work family conflict on employee performance, to analyze the effect of work environment, work stress and work family conflict on the performance of Dinoyo Health Center employees. This type of research uses quantitative methods. The sample used in this study was 55 employees using saturated samples. The data analysis method used in this study was multiple linear regression. The data testing used is simultaneous hypothesis testing (Test F) and partial hypothesis testing (Test t). The results of this study showed that the work environment was partially positive significantly on the performance of Dinoyo Health Center employees. Work stress is partially significant positive for the performance of Dinoyo Health Center employees. work family conflict is partially significant positive for the performance of Dinoyo Health Center employees. Meanwhile, simultaneously the work environment, work stress and work family conflict on the performance of Dinoyo Health Center employees. Keywoard : Work Environtment, Work Stress, Work Family Conflict And Job Performance